DIGITALISASI UMKM DALAM RANGKA AKSES REVOLUSI PEMASARAN DIGITAL UMKM KELURAHAN BUARAN INDAH KOTA TANGERANG - Pratama, Putra; Nurlukman, Adie Dwiyanto; Basit, Abdul (Community Services and Social Work Bulletin, 2024)
The shift from conventional business models to digital business models has become a significant trend among competitors of SMEs. The use of digital media holds great potential to accelerate SMEs' growth. This article aims to socialize the concept of digital marketing to SMEs so that they can effectively leverage it to enhance their competitiveness and business growth. The approach employed in this article involves conducting activities through seminars focused on imparting knowledge, training, and practical assistance to SMEs regarding digital marketing strategies relevant to the context of the Industrial Revolution. By gaining a better understanding of digital marketing, SMEs can attract a broader audience and experience sustainable business growth in this increasingly digital environment.